1984
DOI: 10.1029/ja089ia09p07565
|View full text |Cite
|
Sign up to set email alerts
|

Ion resonances and ELF wave production by an electron beam injected into the ionosphere: Echo 6

Abstract: The interaction with the ionospheric plasma of two separately controllable electron beams injected from the Echo 6 sounding rocket in the auroral zone has been studied using orthogonal electric double probes and other instruments on a separate plasma diagnostics payload. The gun pulses produced a myriad of large electric probe signals covering the entire ion gyro range between dc and 1250 Hz. In particular a signal driven at the 1‐kHz gun frequency and a naturally occurring resonance at 840 Hz near the 799‐Hz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These dimensions are similar to those reported from a joint US/Canadian electron accelerator experiment (Duprat et al, 1983). The Echo 6 flight (Winckler et al, 1984) with a higher beam power showed a disturbed plasma region greater than 140 m of radius. Large disturbed regions of radius up to 800 m were reported by Sagdeev et al (1981) in a lower altitude region.…”
Section: Active Experimentssupporting
confidence: 74%
“…These dimensions are similar to those reported from a joint US/Canadian electron accelerator experiment (Duprat et al, 1983). The Echo 6 flight (Winckler et al, 1984) with a higher beam power showed a disturbed plasma region greater than 140 m of radius. Large disturbed regions of radius up to 800 m were reported by Sagdeev et al (1981) in a lower altitude region.…”
Section: Active Experimentssupporting
confidence: 74%
“…During events 2, 3, 4, and 5 the peaks in Vdif• are associated with specific orientations of the antenna with respect to the velocity and the magnetic field, and therefore can be primarily attributed to shadowing effects. Shadowing effects of this type were observed by Winckler et al [1984] during the Echo 6 experiment. In that experiment, large signals at the payload spin frequency were attributed to shadowing of one probe from a magnetic field aligned plasma flow.…”
Section: The Actual Width Of the Beam Is Unknown; However Previousmentioning
confidence: 99%
“…Active experiments using electron beam sources on board rockets to produce artificial auroras started in 1969 [ Hess et al , 1971; Davis et al , 1971]. This pioneer work was followed by a series of rocket missions such as Echo, for upward injection [ Israelson and Winckler , 1975; Hallinan et al , 1978; Winckler et al , 1984], Excede, for low‐altitude injection [ O'Neil et al , 1978a, 1978b; Paulsen et al , 1990], and TEP/Charge, involving tethers [ Sasaki et al , 1987; Myers et al , 1990; Gilchrist et al , 1990]. Beam sources have also been used onboard the shuttle [ Wilhelm et al , 1984; Beghin et al , 1984; Banks et al , 1987].…”
Section: Introductionmentioning
confidence: 99%